Inhibition of HIV-1 reverse transcriptase by defined template/primer DNA oligonucleotides: effect of template length and binding characteristics. - Idriss, H; Stammers, D (1994)
The interaction of partially double stranded DNA oligonucleotides with HIV-1 RT was studied by investigating their ability to inhibit the homopolymeric poly(rC) directed (dG) synthesis reaction. A 20/18mer oligonucleotide, with a sequence based on the Lys3-tRNA primer region, showed stronger inhibition of the homopolymeric RT reaction than a G/C rich oligonucleotide series lacking or possessing a hairpin moiety. Interaction of the enzyme with the G/C rich oligonucleotides, as determined by IC50 measurements, was insensitive to the extent of the unpaired template region at the 3' or 5' position. Addition of a hairpin moiety, composed of four thymidine bases, onto G/C rich oligonucleotides increase their inhibitory potency (at least six times) and shifted the mode of inhibition of RT to competitive with respect to poly (rC).(dG), which was otherwise mixed (competitive/noncompetitive) for the linear G/C rich and 20/18mer oligonucleotides. The results indicate that interaction of the enzyme with the primer/template stem, but not with the unpaired template region, is an important step in complex formation.